Retrospective analysis of medical costs and resource utilization for severe hypoglycemic events in patients with type 2 diabetes in Japan. Issue 3 (17th November 2018) - Ikeda, Yuika; Kubo, Takekazu; Oda, Eisei; Abe, Machiko; Tokita, Shigeru
Abstract: Aims/Introduction: The present study aimed to describe hospital utilization and examine actual medical costs for severe hypoglycemic events in patients with type 2 diabetes mellitus in Japan. Materials and Methods: Medical resource utilization associated with severe hypoglycemia was evaluated using a receipt database of acute‐care hospitals in Japan. Patients with type 2 diabetes treated with antihyperglycemic agents were included. Severe hypoglycemic events were identified and divided into two groups: with or without hospitalization. Total and attributable medical costs per event were calculated based on the actual medical treatment after severe hypoglycemic events. Attributable costs were estimated from the receipt codes directly associated with the treatment of severe hypoglycemia. Results: In the hospitalized patients, the median length of hospital stay was 11 days, and the median total and attributable medical costs were ¥402, 081 and ¥302, 341, respectively. The majority of the hospitalized patients underwent a radiographic examination and general blood tests. Apart from the hospitalization costs, the costs associated with diagnosis accounted for 29.6% of the total medical costs. In the outpatients, 60.6% visited hospitals only once for the severe hypoglycemic event, whereas 11.4% visited hospitals daily for a week after the severe hypoglycemic event. The mean number of hospital visits of the outpatient after a severe hypoglycemic event was 2.7 ± 2.6 days. The median total and attributable medical costs were ¥265, 432 and ¥4, 628, respectively. Conclusions: Significant medical resources are used for the treatment of severe hypoglycemic events of patients with type 2 diabetes in Japan. Abstract : This article demonstrate the medical costs for severe hypoglycemic events in Japan. We believe that details of medical costs after the event were analysed for the first time in Japan.